Multiscale assembly for tissue engineering and regenerative medicine. Issue 5 (May 2015) - Guven, Sinan; Chen, Pu; Inci, Fatih; Tasoglu, Savas; Erkmen, Burcu; Demirci, Utkan
Highlights: We focus on assembling building blocks from the biomolecular level to the millimeter scale. We provide an overview of techniques to assemble molecules, cells, spheroids, and microgels for bottom-up tissue engineering. We explain driving mechanisms for self- and guided assembly to create micro-to-macro tissue structures. We discuss the advantages and limitations of the assembly techniques. Abstract : Our understanding of cell biology and its integration with materials science has led to technological innovations in the bioengineering of tissue-mimicking grafts that can be utilized in clinical and pharmaceutical applications. Bioengineering of native-like multiscale building blocks provides refined control over the cellular microenvironment, thus enabling functional tissues. In this review, we focus on assembling building blocks from the biomolecular level to the millimeter scale. We also provide an overview of techniques for assembling molecules, cells, spheroids, and microgels and achieving bottom-up tissue engineering. Additionally, we discuss driving mechanisms for self- and guided assembly to create micro-to-macro scale tissue structures.